Legal Policy on Allocating Resources for Pertalite Subsidies: Kaldor-Hicks Efficiency Analysis - Safira Widya Attidhira; Meni Apriani; Romadu Novelino; Jaka Tiwana Alfianda; Faisal Santiago (Jurnal Pembaharuan Hukum, 2026)
This study aims to analyze the legal and political efficiency of the 2024 Pertalite subsidy policy from a legal and economic perspective based on the Kaldor Hicks efficiency principle. The results show that the Pertalite subsidy policy has not fully achieved economic and legal efficiency, as reflected in the negative net social benefits ranging from IDR 8–18 trillion per year. This condition indicates that the resulting social benefits have not exceeded the social costs borne by the state and society. The observed inefficiency is mainly caused by inaccuracies in targeting subsidy recipients, limited data integration between institutions, and a suboptimal legal framework governing the protection and management of digital data in the subsidy distribution system. From a normative perspective, the Pertalite subsidy policy also requires further strengthening to be more aligned with the principles of efficient and fair economic resource management as mandated by Article 33 of the 1945 Constitution of the Republic of Indonesia.